The anthropology of complex economic systems : inequality, stability, and cycles of crisis - Caldararo, Niccolo (Lanham : Lexington Books, 2014)
Today we live in what Ulrich Beck has aptly characterized as a?risk society? shaped by intensifying crises outside of our control and seemingly outside of our comprehension. The master narrative that was supposed to lead us to secular salvation--economics--has proved to be a large part of the problem rather than the much anticipated solution. In The Anthropology of Complex Economic Systems, Niccolo Caldararo offers a much more radical and challenging answer: that the fundamental assumptions on which the modern?science? of economics has been erected are false, and that it is through the medium of anthropology, particularly the relatively neglected field of economic anthropology, that an alternative and sound basis for both the understanding of economic behavior and for the shaping of economic futures can be constructed. Caldararo not only challenges the foundational assumptions of conventional economic theory, but situates economic behavior (something quite different and universal amongst human beings) in both a historical and an ecological context. Contemporary discussions of?sustainability,? especially in the field of development studies, have oddly neglected to look to anthropology. Economic anthropology, is the repository of a vast store of wisdom both about actual alternative and workable economic systems and about their evolution. By drawing on this source, Caldararo builds a model of the evolution of human economies which stir up substantial debate, shows how economic anthropology provides a tool for the interrogation of economic theory, and ties economics to ecology. It has been the rupture of this fundamental relationship that lies at the basis of much of our present crisis and the unsustainable economic patterns that humans have created. By bringing together in a new configuration economic anthropology, ecology, and culture history, Caldararo not only proposes a new model of human social evolution, but equally importantly creates a methodology for speaking to, and against, our present economic and environmental situation. --Amazon.com.
Anthropology and the cosmology of modern economics -- Wants, needs, and the question of surplus versus wealth -- Complexity and stability or stagnation: declining returns and the business cycle -- Wealth, consumption, quality of life and standard of living -- The great debate: economists and anthropologists: the market and society, continued -- Introduction -- Forest fires: origins and myths -- Traditional peoples and fire -- Climate and fire, assessing time's arrow and the antiquity of anthropogenic fire -- Forest managements in modern and traditional society -- The degraded environment and Homo Sapiens -- Co-evolutionary processes and environmental exploitation -- Makeup and nature of forests: fire-adapted species vs "old growth" -- Determining fire history: fire scars, fire histories and thermal alteration -- Insects, biomass reduction and pesticides -- Conclusion: forests and the future of man -- Introduction -- The problem of population and the nature of human society -- Consumerism and sustainability: Japan as an example -- The evolution of modern Japan and its transformation -- The Credit Crisis of 2008 to 20?? -- Ideology and religious precepts and motivations: why people work -- Fundamentalism versus globalism.
Includes bibliographical references (p. 259-314) and index.
Keywords: Economic anthropology; Social structure; Economic history